2017
DOI: 10.1016/j.jiph.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Fecal carriage of MDROs in a population of Lebanese elderly: Dynamics and impact on bacterial fitness

Abstract: Muti-Drug Resistant Organisms (MDROs) are problematic all over the world, especially in Lebanon. High fecal carriage rates of MDR Enterobacteriaceae were reported from Lebanese nursing homes. Some studies show that MDROs have a fitness cost as compared to sensitive isolates. In this study, the competitive growth of MDR Escherichia coli obtained from fecal samples from elderly is assessed. Fecal swabs from ten elderly patients from a Lebanese nursing home were obtained between June and December, 2015. Isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The comparable prevalence between clinical samples from this study, and the prevalence among nursing staff of hospitals without CP would indirectly support the idea that hospital CP practices impart at least some protection against MDRO colonization. We find a similarity between the prevalence data of the hospital still requiring CP to that of a Lebanese nursing home data [55], which is lower than the hospital resistance data described above [54]. This is likely due to the nursing home prevalence being more reflective of community prevalence data as opposed to acute-care hospital data.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The comparable prevalence between clinical samples from this study, and the prevalence among nursing staff of hospitals without CP would indirectly support the idea that hospital CP practices impart at least some protection against MDRO colonization. We find a similarity between the prevalence data of the hospital still requiring CP to that of a Lebanese nursing home data [55], which is lower than the hospital resistance data described above [54]. This is likely due to the nursing home prevalence being more reflective of community prevalence data as opposed to acute-care hospital data.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, a study by Challita et al in 2015 demonstrated an ESBL E. coli prevalence of 7.7% in a Lebanese nursing home [55]. We are not able to explain this lower-than-average prevalence data point, especially in a cohort of institutionalized elderly patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation